EFISIENSI TEKNIS, STRUKTUR BIAYA, DAN PENDAPATAN PENANGKARAN BENIH PADI INBRIDA DI KECAMATAN BUMI RATU NUBAN KABUPATEN LAMPUNG TENGAH - Arif Ardha Kenamon; Fembriarti Erry Prasmatiwi; Lina Marlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The purposes of this research are analyze technical efficiency, factors that affecting technical efficiency, cost structure, break even point, and income of inbred rice seed breeding. Furthermore, this research uses a survey method. The location of the research is chosen purposively in Bumi Ratu Nuban Subdistrict Central Lampung Regency as consideration that there are active and sustainable groups of farmer on inbred rice seed breeding. It should be noted that the number of respondent is 44 farmers which are collected randomly. Additionally, this research was conducted since August-September 2019. The analytical method uses frontier production function, multiple linear regression model, independent sample t-test, cost structure, break even point, and income analysis. The result shows that the level of technical efficiency is quiet efficient by 78.13 percent. Factors that significantly affecting technical efficiency are farming cost, revenue, capital, and land ownership status. The biggest cost component of cost structure for total cost is labor cost by 46.29 percent. Finally, the inbred rice seed breeding is profitable, because BEP value is smaller than revenue, production, and price that obtained by farmers and R/C for total cost is more than 1.Key words: cost structure, inbred rice seed breeding, income, technical efficiency